2017
DOI: 10.1371/journal.pone.0174103
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and role of NKp46 and NKG2A in hepatitis B virus infection

Abstract: Background and AimNatural Killer (NK) cells are involved in the control of viral infection. However, the role of NK cells in chronic hepatitis B (CHB) remains unclear. This study investigated the frequencies and roles of NK cells in CHB, with a focus on activating receptor NKp46 and inhibitory receptor NKG2A.Patients/MethodPeripheral blood lymphocytes were obtained from 71 CHB patients and 37 healthy subjects (HS). The expressions of NKp46 and NKG2A were analyzed using flow cytometry. The role of NKp46-ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
3
12
1
Order By: Relevance
“…This high frequency was also positively correlated with serum ALT and HBV DNA levels. This subset of NK cells showed high cytotoxicity and low production of IFN‐γ and was associated with liver injury, which is in line with the functional dichotomy of NK cells in viral hepatitis …”
Section: Nk Cells and Hbvsupporting
confidence: 69%
See 4 more Smart Citations
“…This high frequency was also positively correlated with serum ALT and HBV DNA levels. This subset of NK cells showed high cytotoxicity and low production of IFN‐γ and was associated with liver injury, which is in line with the functional dichotomy of NK cells in viral hepatitis …”
Section: Nk Cells and Hbvsupporting
confidence: 69%
“…Studies that evaluated the level of NKG2A, as inhibitory receptor, on NK cells of CHB patients show discrepancies, like other receptors (Table ). Some studies show elevated level of NKG2A, while others show similar or even decreased level of this receptor on NK cells of CHB patients compared with that of healthy subjects . Results of in vitro studies showed that blockade of NKG2A by monoclonal antibodies enhanced cytotoxicity of NK cells isolated from active CHB patients; furthermore, blockade of NKG2A or its ligand Qa‐1 considerably promoted HBV clearance in HBV‐carrier mice .…”
Section: Nk Cells and Hbvmentioning
confidence: 99%
See 3 more Smart Citations